The concept of educational quality and its criteria - Muhammadjonov Muslimbek (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the concept of educational quality and several of its key criteria. It also provides an analysis of the factors influencing the quality of education in higher educational institutions, along with conclusions based on the conducted study.